Analysis of the Impact of Environmental Microplastics on Human Health from the Perspective of Modern Environmental Health - Triana Srisantyorini; Endang Pertiwiwati; Sahari Bulan; Ismed Ismed; Elvina Triana Putri (Mandalika Institute, 2026)
Environmental microplastics have become a critical environmental health concern, yet the extent of their impact on human health remains insufficiently resolved due to heterogeneity in particle properties, exposure pathways, and methodological translation. This study aims to synthesize how environmental microplastics may affect human health from the perspective of modern environmental health, with particular attention to exposure realism, plausibility of mechanisms, and uncertainty in risk interpretation. Methodologically, it employs a library-based research design using primary and secondary literature sources related to microplastics, human health, and modern environmental health concepts, followed by content analysis to identify recurring thematic patterns and relationships. The reviewed literature data indicate consistent evidence of multi-route exposure pathways and recurring mechanistic hypotheses such as inflammation and oxidative stress, while significant uncertainty persists in dose estimation, mixture effects, and comparability across studies. The study concludes that microplastics are plausibly health-relevant but require strengthened translational evidence to support decision-grade risk assessments within modern environmental health practice.